A STUDY ON ENTREPRENEURSHIP DEVELOPMENT IN INDIA – AN OVERVIEW - RAJAMANI, S. (International Journal of Psychosocial Rehabilitation, 2020)
In India, entrepreneurship can stop solution for addressing the major problems of unemployment and poverty. Various initiatives have been taken by the government from time to time for entrepreneurship development in the country such as Industrial Policies and Five-Year Plans specifically focusing on the growth of small scale sector, setting up of Special Economic Zones (SEZS), setting up of Entrepreneurship Institutions, organizing Entrepreneurship Development Programmes (EDPs) and various Government Programmes and Schemes for the promotion of entrepreneurship. Every country, whether developed or developing, needs entrepreneurs. Whereas, a developing country needs entrepreneurs to initiate the process of development, the developed one needs entrepreneurship to sustain it. In the present Indian context employment opportunities in public sector and large-scale sector are shrinking, and vast opportunities arising from globalization are waiting to be exploited: entrepreneurship can really take India to the heights of becoming a super economic power. This paper presents an overview of an entrepreneurship development in India.